Fiqih Indigenous Indonesia dan Relevansinya dalam Pendidikan Pesantren: Pendekatan Fiqih Aplikatif dalam Kitab Fashalatan K.H.R. Asnawi Kudus - Zuhri, Achmad; Hanifa, Aulia Nisa (Santri: Journal of Pesantren and Fiqh Sosial, 2025)
This study aims to examine the applicative approach in the Fashalatan book by K.H.R. Asnawi Kudus as well as its relevance and contribution to Islamic education in Indonesia, focusing on four main aspects: the position of Fashalatan as a work of Nusantara scholars, its role as an indigenous fiqh book rooted in local tradition, the concept of applicative worship fiqh in its presentation, and its contribution to education in pesantren and traditional communities. The method used is qualitative research with literature review and content analysis techniques, sourcing from the original Fashalatan text, classical fiqh literature, and scholarly works related to traditional Islamic education. The results show that Fashalatan successfully simplifies Shafi’i fiqh into a worship guide that is easy to understand and practice by using local language and Arabic Pegon script, facilitating access for the general Muslim community. The book not only strengthens the preservation of Nusantara Islamic traditions by harmonizing Islamic law and local culture but also serves as an effective and relevant medium for applicative fiqh education in pesantren and the wider society, thereby supporting the continuity of scholarly traditions and contextual worship practices in Indonesia.